Clean Technologies Toward a Sustainable Future Physicochemical, Biochemical and Biotechnological Approaches - Verma, Pradeep; Shah, Maulin P. (IWA Publishing, 2023)
Increasing global population growth and the continued exploitation of land, water and other natural resources is causing the release of harmful gases and toxic compounds into the environment. To combat this pollution and mitigate its impact, a number of physicochemical, biochemical, and biotechnological approaches have been developed. Each chapter of this book focuses on one specific technology, discussing its principle, methodology, recent advances, limitations, technological and economic feasibility, and its prospects for the future.